The net delusion : the dark side of internet freedom - Morozov, Evgeny 1984- (New York, N.Y. : Public Affairs, 2011)
The Google doctrine -- Texting like it's 1989 -- Orwell's favorite lolcat -- Censors and sensibilities -- Hugo Chavez would like to welcome you to the spinternet -- Why the KGB wants you to join Facebook -- Why Kierkegaard hates slacktivism -- Open networks, narrow minds : cultural contradictions of internet freedom -- Internet freedoms and their consequences -- Making history (more than a browser menu) -- The wicked fix.